Cross-talk between macrophages and atrial myocytes in atrial fibrillation - Sun, Zewei (Basic Res Cardiol, 2016)
Increased macrophage accumulation occurs in the atria of patients with atrial fibrillation (AF). However, the phenotype and functions of the macrophages in AF remain unclear. We investigated the macrophage-atrial myocyte interaction in AF patients and found that the increased macrophages were mainly pro-inflammatory macrophages (iNOS(+), Arg1(−)). Tachypacing of HL-1 atrial myocytes also led to pro-inflammatory macrophage polarization. In addition, lipopolysaccharide (LPS)-stimulated pro-inflammatory macrophages-induced atrial electrical remodeling, evidenced by increased AF incidence and decreased atrial effective refractory period and L-type calcium currents (I (Ca-L)) in both canine and mouse AF models. Depletion of macrophages relieved LPS-induced atrial electrical remodeling, confirming the role of pro-inflammatory macrophages in the pathogenesis of AF. We also found that the effect of LPS-stimulated macrophages on atrial myocytes was mediated by secretion of interleukin 1 beta (IL-1β), which inhibited atrial myocyte quaking protein (QKI) expression. IL-1β knockout in macrophages restored the LPS-stimulated macrophage-induced inhibition of QKI and CACNA1C (α1C subunit of L-type calcium channel) in atrial myocytes. Meanwhile, QKI overexpression in atrial myocytes restored the LPS-stimulated macrophage-induced electrical remodeling through enhanced binding of QKI to CACNA1C mRNA, which upregulated the expression of CACNA1C as well as I (Ca-L). In contrast, QKI knockout inhibited CACNA1C expression. Finally, using transcription factor activation profiling plate array and chromatin immunoprecipitation, we revealed that special AT-rich sequence binding protein 1 activated QKI transcription. Taken together, our study uncovered the functional interaction between macrophages and atrial myocytes in AF. AF induced pro-inflammatory macrophage polarization while pro-inflammatory macrophages exacerbated atrial electrical remodeling by secreting IL-1β, further inhibiting QKI expression in atrial myocytes, which contributed to I (Ca-L) downregulation. Our study demonstrates a novel molecular mechanism underlying the pathogenesis and progression of AF and suggests that QKI is a potential therapeutic target. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00395-016-0584-z) contains supplementary material, which is available to authorized users.